Frequency Of Cyp3a5 (A6986g) Gene Polymorphism In Patients With BA, COPD, And ACO - Raufov A.A.,; FayzullaevaN.Ya.; Ruzibakieva M.R. (Universitas Muhammadiyah Sidoarjo, 2022)
Asthma and COPD are the most common chronic respiratory diseases, each with a specific pathophysiology. Usually, asthma is characterized by chronic inflammation of the airways with reversible symptoms, while COPD is characterized by persistent respiratory changes in the bronchopulmonary system. However, patients can sometimes have clinical features of both diseases, and this condition is called the asthma-COPD overlap (ACO) recommended by the joint guidelines of GINA (Global Strategy for the Management and Prevention of Asthma) and GOLD (Global Initiative on Chronic Obstructive Pulmonary Disease). According to this guide, ACOis characterized by